Efektivitas Bahan Ajar Buku Panduan Pembelajaran Kebencanaan Kabupaten Klaten Terhadap Peningkatan Hasil Belajar Siswa Pada Bencana Gempa Bumi Melalui Strategi Role Playing Di Sma Negeri 1 Klaten - Sanusi, Ihwan; , Drs. Suharjo, M.S (2016)
This research aims (1) to know the effectiveness teaching material of learning guilding book about disaster in Klaten regency in Senior High School 1 Klaten. (2) to know the result of learner's study of using teaching material of learning guilding book about disaster in Senior High School 1 Klaten. This research is experiment reasearch with quantitative approach. Using one group pre test post test design. Quantitative data based on giving the questions pre test and post test in the first experiment class and second experiment class. the learning strategy on first experiment class is role playing and the convensional strategy on second experiment class. The technique of analyzing the data is Paired Sample t-Test. The researcher get some result that there are different of increasing study from average grade of pre test and post test in first experiment class and second experiment class.The pre test average grade of first experiment class are 78 % and the post test average grade are 90,4 %. Then, the pre test average grade of second experiment class are 70 % and the post test average grade are 77,2 %. It's means that the teaching material of learning guiding book about disaster in Klaten regency is affective thai pointed with increasing learner's study by role playing strategy in disaster of earthquake topic. Keyword: Effectiveness of teaching material, study result, role playing.